Pengaruh Health Education Terhadap Perilaku Wanita Usia Subur Dalam Pemeriksaan Infeksi Menular Seksual di Wilayah Kerja Puskesmas Jumpang Bar - Mustarin, Yanti; Kurnaesih, Een; Yusriani, Yusriani (Window of Health : Jurnal Kesehatan, 2018)
The handling of the case of IMS is a service with an IMS-related syndrome, or with positive results on the lab checks for one or more IMS. IMS case handling component should be done in plenary the purpose of this research is to analyze the effect of Health Education against women fertile age behavior in an examination of sexually transmitted infection (STI) Clinics in the region Jumpang The New City Of Makassar. The research design used was a quasi-experimental design pre-post with comparison group which attempts to reveal the effectiveness of free variables bound by involving variable against the control group and group interventions with the number of each sample as many as 37 Wus The research results obtained that health education effect on the knowledge, attitudes, and actions of the WUS in the examination of STI health centers in the region Jumpang a new City of Makassar from the results of the test statistic T-Test p sig = 0.000 < 0.05. Health Education in the examination of IMS in an attempt early detection of sexually transmitted diseases influence the improvement of knowledge, attitude and action become more positive, authorized agencies can be expected to do so in a wider range of and better quality.